(untitled) (Journal of Small Business Strategy (archive only), 2014)
This study examines whether or not having an internal or external strategic focus interacts with prior experience in small business to impact perceived organizational performance. Utilizing a sample of 237 small business owners from the southeast U.S., a factorial ANOVA and Regression Analysis were used to test hypotheses related to these constructs. Results indicated that utilizing an internal focus was associated with higher performance among both experienced and inexperienced small business owners; however, an external focus was only positively related to performance for inexperienced business owners. No overall difference in performance was found for experience itself.